PENGEMBANGAN VIDEO TUTORIAL MENJAHIT BELAHAN DUA LAJUR PADA PEMBUATAN BUSANA RUMAH FASE E DI SMK NEGERI 1 KALITENGAH - Wukir Cahyandari; Imami Arum Tri Rahayu (JURNAL ILMIAH NUSANTARA, 2026)
This study focuses on the development of a tutorial video as a learning medium for sewing a double-bound placket in homewear. The objectives of this study are to (1) describe the feasibility of the tutorial video as a learning medium for sewing a double-bound placket in homewear and (2) determine students' learning outcomes after using the tutorial video. This study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were 32 Phase E students of the Fashion Design and Production Program at SMK Negeri 1 Kalitengah. The data collection instruments included material expert validation sheets, media expert validation sheets, and a performance test. The data were analyzed using descriptive quantitative analysis based on the average validation scores. The results showed that (1) the tutorial video obtained an average feasibility score of 3.71, which falls into the highly feasible category, and (2) the students achieved an average score of 87 with 100% learning mastery, meeting the school's Minimum Learning Achievement Criteria (KKTP).